Characteristics of Charcoal Briquettes, Activated Charcoal, and Liquid Smoke from Palm Shells (Elais Guineensis Jacq) - Rindayatno; Finsya Annisa Cahya Shafiera; Baktiriani Banda Padang; Apriyanti Nugrahaningrum; Agus Nur Fahmi (PT FORMOSA CENDEKIA GLOBAL, 2022)
This study contains three products made from palm shells, namely charcoal briquettes, activated charcoal, and liquid smoke. Aims to know and analyze the characteristics of the three products. Charcoal briquettes are made by printing palm shell charcoal powder and then testing for density, moisture content, compressive toughness, volatile matter, ash content, bound carbon content, and heating value. Activated charcoal uses shell charcoal powder which is activated by soaking for 5 hours in 5% hydrochloric acid (HCl) then tested for its adsorption on spills of used lubricant. Liquid smoke from oil palm shells is obtained by pyrolysis process and multilevel purification and then the yield, pH value, specific gravity, and color are measured. Palm shell charcoal briquettes had the following values: density 0.691 g/cm3, moisture content 4.935%, compressive strength 13.444 kg/cm2, volatile matter content 42.700%, ash content 3.000%, bonded carbon content 62.200% and heating value 6070.667 cal/ g. Palm shell activated charcoal has the ability to adsorb used lubricants up to 1.505 times stronger than activated charcoal with a bonded carbon content of 90.667%. Grade 3 palm shell liquid smoke produces a yield of 12.61%, a pH of 3.58, a specific gravity of 1.004, and a dark brown color. Grade 2 produces 8.91% yield, pH 3.24, specific gravity 1.004, and yellow color. Grade 1 produces 6.30% yield, pH 2.99, specific gravity 1.001, and pale yellow color